Necessary optimal conditions for singular control in the discrete systems with distributed control - Janušauskaitė, Nijolė (Lietuvos matematikos rinkinys, 2003)
Necessary conditions for singular control of the Mayer form's functional in the discrete systems with distributed control are obtained.